EKSPLORASI FAKTOR SUMBER DAYA MANUSIA BERBASIS KEWIRAUSAHAAN (HRBE) - Rusman Frendika; Isniar Budiarti (Jurnal Inovasi Penelitian, 2022)
Entrepreneurial opportunities arise when certain individuals have insight into the value of resources that others do not have. Entrepreneurial vigilance, entrepreneurial knowledge, and the ability to coordinate resources as their own. This study is intended to advance our understanding of human resource factors based on entrepreneurship. A total of 175 questionnaires were sent to HRM managers, and 150 received back is 86% response rate of 175 SMEs. Factor analysis is used to assess the underlying structure of human resources. Responses to the HRM and entrepreneurship items were analyzed using multivariate analysis of variance (MANOVA). The results of this study identify that the human resource factors that greatly influence entrepreneurship are Entrepreneurial Ability and Entrepreneurial Innovation, Entrepreneurial Intelligence, Entrepreneurial Knowledge, and Entrepreneurial Competence.